Islamic microfinance branchless banking model in Indonesia - Santoso, Bedjo; Mohd Israil, Khaliq Ahmad (IIUM Institute of Islamic Banking and Finance (IIiBF)., 2016)
ICT has been recently developed into a digital sustainable collaborative networking (DCN) platform, and it is expected to be capable of demonstrating the building of social and economic welfare, particularly in crafting innovations to facilitate marginal society.This research attempts to develop an innovative platform of an empirical ICT application a branchless banking form based on ICT Model. The application of Branchless banking model is expected to address the poverty problem which is significantly high in Indonesia. Indonesia is known for it’s heterogeneous values in terms of its areas, ethics, traditions, customs, communities, and local wisdom. The newly introduced application of a mobile payment system is parallel to the vision, and mission upheld by the government. Currently, most literature and practices are just partial. The community model based on Islamic microfinance and Cooperatives is neglected. Therefore, this research aims to design branchless banking in terms of financial inclusion involving Islamic microfinance and Cooperatives. Furthermore, this paper also attempts to test to what extent the proposed model is viable in the current system. This study employs a qualitative approach by conducting an interview with the stakeholders and a deductive method is used to explore and design the proposed model. The finding exhibit that branchless banking based on an Islamic microfinance and a Cooperative model is more flexible and easily acceptable while crafting a deal with Indonesian. In addition, the proposed model is viable in the current system. By implementing this model, the economy can be strengthened toward national unity and a welfare state.